2017
DOI: 10.3390/w9060381
|View full text |Cite
|
Sign up to set email alerts
|

Optimising Fuzzy Neural Network Architecture for Dissolved Oxygen Prediction and Risk Analysis

Abstract: Abstract:A fuzzy neural network method is proposed to predict minimum daily dissolved oxygen concentration in the Bow River, in Calgary, Canada. Owing to the highly complex and uncertain physical system, a data-driven and fuzzy number based approach is preferred over traditional approaches. The inputs to the model are abiotic factors, namely water temperature and flow rate. An approach to select the optimum architecture of the neural network is proposed. The total uncertainty of the system is captured in the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…DDM have the potential to simulate any biological or methanotrophic culture performance whilst considering all the needed factors that may affect the culture performance. Interestingly, these factors can be considered and simulated in a DDM, even though, the impact of these conditions are not fully understood or can be mathematically described (Khan and Valeo, 2016a, 2017a, 2017b. In other words, DDMs allow to model a system based on the available input data (e.g., the KBM coefficients) and the required output data (e.g., methanotrophic biomass).…”
Section: Data-driven Models For Simulating Methanotrophic Culturementioning
confidence: 99%
See 1 more Smart Citation
“…DDM have the potential to simulate any biological or methanotrophic culture performance whilst considering all the needed factors that may affect the culture performance. Interestingly, these factors can be considered and simulated in a DDM, even though, the impact of these conditions are not fully understood or can be mathematically described (Khan and Valeo, 2016a, 2017a, 2017b. In other words, DDMs allow to model a system based on the available input data (e.g., the KBM coefficients) and the required output data (e.g., methanotrophic biomass).…”
Section: Data-driven Models For Simulating Methanotrophic Culturementioning
confidence: 99%
“…Similarly, identifying the amount of data used for training, validation, and testing is a key factor as using a small amount of data for training can result in poor model performance and using more data will result in less data set for validating and testing (which may be insufficient for model inference). Typically, both NH and amount of data used for data division are selected based on a trial and error method, however a coupled method to identify the optimum NH and data division has been proposed (Khan and Valeo, 2017b). In this research, the previously suggested method has been followed with some minor adjustments to fit our model and is described below.…”
Section: Ann Architecture Optimization and Uncertainty Analysismentioning
confidence: 99%
“…ANN model uncertainties come from the choice of ANN architecture (i.e., number of hidden layers, number of neurons, choice of activation function, type of training algorithm and data partitioning), as well as the performance metric chosen. Due to the data-driven nature of these models, propagating these uncertainties is easier [78,79]. One method of quantifying this uncertainty is by using fuzzy numbers to quantify the total uncertainty in the weights, biases and output of the ANN [78,80,81].…”
Section: Geosciences 2019 9 X For Peer Review 13 Of 22mentioning
confidence: 99%
“…Due to the data-driven nature of these models, propagating these uncertainties is easier [78,79]. One method of quantifying this uncertainty is by using fuzzy numbers to quantify the total uncertainty in the weights, biases and output of the ANN [78,80,81]. This technique is useful for dealing with limited or imprecise datasets and can be used to conduct risk analysis [82].…”
Section: Geosciences 2019 9 X For Peer Review 13 Of 22mentioning
confidence: 99%
See 1 more Smart Citation